Efecto de la masticación de la hoja de coca sobre las estructuras de la cavidad oral - Lucas Espeza, Linda Patricia (2019)
Chewing coca leaves is a rooted habit in several localities in Latin America, especially in the Andean areas. This habit has been related to possible alterations in various components of the oral cavity. The purpose of this review is to describe the changes that oral cavity structures undergo by chewing coca leaves. Several studies will be presented where it is found that the frequency in addition to the alkaline substance used in chewing coca leaf affects the hard and soft tissues of the oral cavity. It is concluded in the review that chewing coca leaf leads to pigmentation of oral mucosa, dental wear and periodontal diseases.